Представьте в виде произведения выражения : 1)a^4-(7b-a^2)^2 2)(4x-9)^2-(2x+19)^2 3)(a+b+c)^2-(a-b-c)^2

ARTiStlll ARTiStlll    3   21.08.2019 18:50    1

Ответы
ledzep ledzep  05.10.2020 09:51
1)a^4-49b+14ab^2-a^4=-49b+14ab^2=14ab^2-49b=7b(2a^2-7)
2)(4x-9-(2x+19))(4x-9+2x+19)=(4x-9-2x-19)(6x+10)=(2x-28)(6x+10)=2(x-14)*2(3x+5)=4(x-14)(3x+5)
3)(a+b+c-(a-b-c))(a+b+c+a-b-c)=(a+b+c-a+b+c)2a=2(b+c)2a=4a(b+c)
ПОКАЗАТЬ ОТВЕТЫ
Azalia1324 Azalia1324  05.10.2020 09:51
1)a^4-49b+14ab^2-a^4=-49b+14ab^2=14ab^2-49b=7b(2a^2-7)
2)(4x-9-(2x+19))(4x-9+2x+19)=(4x-9-2x-19)(6x+10)=(2x-28)(6x+10)=2(x-14)*2(3x+5)=4(x-14)(3x+5)
3)(a+b+c-(a-b-c))(a+b+c+a-b-c)=(a+b+c-a+b+c)2a=2(b+c)2a=4a(b+c)
ПОКАЗАТЬ ОТВЕТЫ
Adel3004 Adel3004  05.10.2020 09:51
1)a^4-49b+14ab^2-a^4=-49b+14ab^2=14ab^2-49b=7b(2a^2-7)
2)(4x-9-(2x+19))(4x-9+2x+19)=(4x-9-2x-19)(6x+10)=(2x-28)(6x+10)=2(x-14)*2(3x+5)=4(x-14)(3x+5)
3)(a+b+c-(a-b-c))(a+b+c+a-b-c)=(a+b+c-a+b+c)2a=2(b+c)2a=4a(b+c)
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра